Assessment of Technical Impacts of EV Charging to Malaysian Distribution Grid - Hashim M.S.; Ying Yong J.; Ramachandaramurthy V.K.; Mansor M.; Tan K.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Automation; DC transformers; Electric automobiles; Fast charging (Batteries); Intelligent systems; MATLAB; Process control; Transformer substations; Connection schemes; Distribution grid; Distribution systems; Electric vehicle charging; Matlab/Simulink software; Substation transformers; Technical guidelines; Transportation sector; Electric power transmission networks